Experimental Investigations on Concrete with Fly Ash and Marble Powder for Paver Blocks - Meera, Miss; Durga Vara Prashad, B; Gupta, Supratic (International Journal of Engineering and Technology, 2018)
The construction industry is capable of absorbing large amounts of wastes by utilizing them in other useful products. Thermal power plants and marble industries produce huge quantitiesÂ  of bi-products which causes environmental problems. Utilization of these in concrete will save natural resources to some extent and solve the disposal. Interlocking concrete block pavements are simple to construct and maintain. The main objective of this research is to develop an eco-friendly paver block while considering the economy as a defining parameter. In this research, experimental investigations were carried out on the paver blocks to know the feasibility of using fly ash and marble powder. For paving block concrete, it is partly replaced with cement and aggregates with fly ash and waste marble powder. Various tests for mechanical and durability properties were conducted. All the properties were improved when compared to the control mix. Utilization of fly ash and marble powder in concrete reduces the cost of paver blocks and making it economical and eco-friendly.Â